Place of Work and Level of Satisfaction with the Lives of Polish Nurses - Anna Bartosiewicz; Małgorzata Nagórska (MDPI AG, 2020)
Practicing as a nurse may be a factor influencing the overall level of satisfaction with life. The aim of the study was to assess the level of satisfaction with nurses' lives in relation to the place of employment. The research was conducted among nurses working in hospitals, primary health care, and outpatient specialist care. The study was carried out with the use of the satisfaction with life scale (SWLS) scale. Statistical analysis included a quantitative and qualitative approach to life satisfaction of the nurses surveyed. The impact of independent variables, measured on nominal (qualitative) scales on the results of the SWLS scale in quantitative terms, was assessed using one-way analysis of variance (ANOVA). Pairwise comparisons were assessed with the assumption of equality of variance with the Tukey honestly significant difference test. The level of satisfaction with life of the surveyed nurses was average. The place where nurses worked significantly influenced the level of life satisfaction. Nurses working in a hospital had a high level of satisfaction with life more so than nurses working in primary care or outpatient specialist care. The workplace is a factor that significantly differentiates the level of life satisfaction of the surveyed nurses.